City Heating Network Dispatching and Management Information System - YAO XiaoFeng; ZHAO Rui; XU HuiPu (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In this paper, the underlying control network was built up in view of the actual operation of heating network through applying the intelligent nodes based on CAN bus, and the data acquisition and control functions were completed to realize the local intelligent control, then adapt the change of outdoor temperature and the operating condition of heating network, and achieve the unattended purpose ultimately. The seamless connection between the underlying control network (CAN network) and the upper management network (Internet) was implemented by using embedded network gateway and reliable VPN technology,  the operating parameters of the heat exchange stations can be remote monitored in real-time. the function configuration of the underlying intelligent nodes   were achieved combines with the needs of the industrial field to realize the automatic control of the thermal parameters, software framework was put up based on FIX monitoring software to complete the module design such as graphical interface, real-time database, history data trends and reports design etc. The system has the characters such as great flexibility, simple human-machine interface, stable and reliable in practical application, which has broad applicability and be worth popularizing. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.1206